Experimental analysis of fluid-structure interaction phenomena on a vertical flexible cylinder: modal coeficients and parametric resonance. - Salles, Rafael (2016)
Oil and gas exploitation in deep waters has become more than just a profit business to be a daily necessity, since the world energy matrix is based on fossil components. Risers are offshore structures that are intimately linked with oil and gas exploitation and those are subjected to a great variety of effects in field, e.g., marine currents, Vortex Induced Vibration (VIV), heave motion caused by gravitational waves, non-linear contact with the sea floor, and many others. Riser dynamics is essentially non-linear and experimental tests in real scale are almost impossible due to a great variety of control parameters acting concomitantly. Small-scale models are a better experimental approach. Nevertheless, there are many structural and hydrodynamical parameters to be evaluated. Considering only vertical risers in the present work, Galerkin\'s modal decomposition is used in order to reduce the dynamics of a vertical flexible cylinder to a few linear modes in which the majority of energy and information are contained. From the modal analysis, added mass and structural parameters damping of a vertical flexible cylinder using data obtained from free-decay tests performed both in water and in air are evaluated. Finally, a modal Mathieu-Hill oscillator with non-linear damping is constructed and, based on aStrutt diagram, modal stability under parametric resonance is discussed.